Local People's Attitudes Towards Mangrove Conservation Effort in East Kalimantan, Indonesia - Tahir, Hikmah (Interdisciplinary Social Studies, 2023)
Background: Human activity has accelerated the degradation of mangrove forests in Southeast Asia, especially in Indonesia. The Government has encouraged conservation efforts towards the woods to cope with this problem. Participation of local people is considered necessary nowadays to understand their attitudes related to such issues. Studies are limited in Indonesia's context, especially in East Kalimantan province's case concerned with a heterogeneous community regarding socioeconomic and limited access to conservation activities. Aim: This study aims to understand how local people could have different participation and willingness to participate (WTP) as the embodiment of their attitudes towards conservation activities and how their reasons are associated with the heterogenous characteristics by taking the location of Margomulyo Mangrove Conservation Area (MMCA) Balikpapan, East Kalimantan. Method: This study uses a qualitative approach combining interviews, observation, and document collection methods. The data is analyzed inductively using coding stages from Miles, Huberman, and Saldaña. Findings: This study reveals positive attitudes by different participation from local people that presented as a heterogenous community. Reasons for involvement vary and are associated mainly with occupation, experiences in mangrove conservation activities that gave them access to the projects, and good networks among local people. Meanwhile, an excellent social relationship contributes to the WTP of local people in the projects with different preference types of activities. This study's findings suggest equitable management for local people by the Government by considering adequate social capital that already exists in the community.